2020
DOI: 10.1155/2020/2018162
|View full text |Cite
|
Sign up to set email alerts
|

ZiYinHuaTan Recipe Inhibits Cell Proliferation and Promotes Apoptosis in Gastric Cancer by Suppressing PI3K/AKT Pathway

Abstract: In recent years, traditional Chinese medicine has played an important role in the treatment of gastric cancer in China. ZiYinHuaTan (ZYHT) recipe was developed for advanced gastric cancer and had shown its promising value in the clinic. In this study, we explore the effect of ZYHT on gastric cancer in vitro and in vivo. ZYHT can inhibit tumor growth and improve the general condition of mice in subcutaneous transplantation nude mice models of gastric cancer. And ZYHT can also inhibit cell proliferation and bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…This method can reduce the activity of gastric cancer cells in nude mice in vitro and in vivo, but this model can only treat one person at a time. Samples can be processed in batches using machine learning to achieve popularization effects [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method can reduce the activity of gastric cancer cells in nude mice in vitro and in vivo, but this model can only treat one person at a time. Samples can be processed in batches using machine learning to achieve popularization effects [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, they found that ZYHT may exert anti-cancer effect mainly through PI3K/AKT signaling pathway related with potential mechanism for proliferation and apoptosis. These results suggest that ZYHT can be used as a method for the treatment of developed gastric cancer [ 96 ]. Schematic diagram of anti-metastatic mechanisms of each herbal medicine in gastric cancer is elucidated in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Especially, AF on colorectal cancer, JLC on gastric cancer and SN, RP, TIF on breast cancer showed the efficacy of arrest of cell cycle in the G2/M stage [ 63 , 93 , 120 , 125 , 127 ]. On the other hand, Jingfukang on lung cancer, ZJW on colorectal cancer, XTHW, ZYHT on gastric cancer and SCB on liver cancer presented the efficacy of arrest of cell cycle in (G0)/G1 stage [ 56 , 84 , 94 , 96 , 101 ]. In addition, all clinical studies have shown a significant increase in survival time in the group of metastatic cancer patients administered with herbal medicine.…”
Section: Discussionmentioning
confidence: 99%
“…miR-489 functions as an oncogene can significantly promote GC cell (SGC7901 and MKN45) proliferation, invasion, and migration and effectively block the activation of PI3K/AKT pathway [ 26 ]. Yu et al found that Zi Yin Hua Tan (ZYHT) recipe could inhibit tumor growth and cell proliferation and promote apoptosis in gastric cancer by suppressing the PI3K/AKT pathway [ 27 ]. Liu et al confirmed that ginsenoside Rg3 (Rg3), an herbal medicine, also a component of SJZT, can ameliorate gastric precancerous lesions in Atp4a-/- mice via inhibition of glycolysis through the PI3K/AKT pathway [ 28 ].…”
Section: Discussionmentioning
confidence: 99%